2008
DOI: 10.1111/j.1445-5994.2008.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the treatment of established fungal infections

Abstract: Evidence-based guidelines for the treatment of established fungal infections in the adult haematology/oncology setting were developed by a national consensus working group representing clinicians, pharmacists and microbiologists. These updated guidelines replace the previous guidelines published in the Internal Medicine Journal by Slavin et al. in 2004. The guidelines are pathogen-specific and cover the treatment of the most common fungal infections including candidiasis, aspergillosis, cryptococcosis, zygomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 206 publications
(463 reference statements)
0
31
0
5
Order By: Relevance
“…These recommendations update those published previously 1 and are based on antifungal agents currently licensed for use in Australia. Invasive yeast diseases are categorised under the headings of invasive candidiasis, cryptococcosis and uncommon yeast infections.…”
Section: Introductionmentioning
confidence: 61%
“…These recommendations update those published previously 1 and are based on antifungal agents currently licensed for use in Australia. Invasive yeast diseases are categorised under the headings of invasive candidiasis, cryptococcosis and uncommon yeast infections.…”
Section: Introductionmentioning
confidence: 61%
“…Among the new broad-spectrum azoles, voriconazole has demonstrated favorable results in candidemia, 27 and is a standard for the first-line treatment of acute invasive aspergillosis. 13,[28][29][30][31] Extensive clinical experience has also shown that voriconazole is effective against Scedosporium spp. and Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Zygomycetes belong to the order of Mucorales comprising the genera of Rhizopus, Mucor, Rhizomucor, Absidia and Cunninghammella. Examples of pathogenetic species are Rhizopus arrhizus, Mucor circinelloides, Rhizomucor pusillus, Cunninghamella bertholletia and Absidia corymbifera [31]. Along with malignancies, immuno-suppressive therapy including high-dose corticosteroids, diabetes, iron overload and treatment with the iron chelator deferoxamine, which can be used as a siderophore by the fungi, are major risk factors for the acquisition of zygomycosis.…”
Section: Rare Mould Infectionsmentioning
confidence: 99%
“…Posaconazole is an option for salvage therapy but is not eff ective against Absidia corymbifera and Rhizopus oryzae. Iron starvation by the iron chelator deferasirox in combination with lipid-formulated amphotericin B and hyperbaric oxygen are evaluated in clinical trials [31]. Infections with Scedosporium apiospermum are treated with voriconazole.…”
Section: Rare Mould Infectionsmentioning
confidence: 99%